2021
DOI: 10.3389/fonc.2021.725264
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Validation of a Platinum Sensitivity Predictive Model With Multiple Genomic Variations for Epithelial Ovarian Cancer

Abstract: Platinum-based chemotherapy is still the standard of care after cytoreductive surgery in the first-line treatment for epithelial ovarian cancer. This study aims to integrate novel biomarkers for predicting platinum sensitivity in EOC after initial cytoreductive surgery precisely. To this end, 60 patients were recruited from September 2014 to October 2019. Based on the duration of progress-free survival, 44 and 16 patients were assigned to platinum-sensitive and platinum-resistant group, respectively. Next gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…The presence of two other signatures (SBS10b and SBS21) in patients’ tumors showed a trend toward poorer OS as well. This is in contrast to results of Zheng et al (2021) who published significant associations of the SBS10a presence with worse response to platinum and shorter progression-free survival of EOC patients ( Zheng et al, 2021 ). A recently published whole-genome sequencing study reported data on eight selected SBSs representing aging, platinum exposure, and defective homologous recombination ( de Witte et al, 2022 ), of which none associated with the resistance status or survival of EOC patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The presence of two other signatures (SBS10b and SBS21) in patients’ tumors showed a trend toward poorer OS as well. This is in contrast to results of Zheng et al (2021) who published significant associations of the SBS10a presence with worse response to platinum and shorter progression-free survival of EOC patients ( Zheng et al, 2021 ). A recently published whole-genome sequencing study reported data on eight selected SBSs representing aging, platinum exposure, and defective homologous recombination ( de Witte et al, 2022 ), of which none associated with the resistance status or survival of EOC patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Corroborating our results, previous reports have also documented high rates of TP53 mutations in EOC tumors, especially of the HGSC subtype ( Ahmed et al, 2010 ; Patch et al, 2015 ), and their potential to predict chemoresistance ( Brachova et al, 2015 ). However, recent studies did not find an association of TP53 mutations with EOC recurrence using the WES approach ( Li et al, 2019 ; Zheng et al, 2021 ). Targeting of the p53 pathway by the WEE1 inhibitor AZD1775 was shown to improve the efficacy of carboplatin in TP53 -mutated EOC tumors ( Leijen et al, 2016 ), and other options are currently being discussed ( Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, recently, increasing evidence implicates that "BRCAness" phenotype, including alterations in other homologous recombination repair genes (8) and/or homologous recombination deficiency (HRD) (9), could also confer sensitivity to platinum-based therapy. By utilizing targeted next-generation sequencing, Zheng and her colleagues have established a platinum-sensitivity predictor based on the whole-genome duplication, loss of heterozygosity, and mutational signature (10). Meanwhile, gene expression was also suggested to have close association with the platinum sensitivity in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 Epithelial ovarian cancer (EOC) is the most common and lethal among all kinds of OC. 4,5 Serous ovarian carcinoma (SOC) makes up the most common histological subtype of EOCs and is divided into High grade serous ovarian carcinoma (HGSOC) and Lowgrade serous ovarian carcinoma (LGSOC). 6,7 Extensive cytoreductive surgery combined with platinum-based chemotherapy is currently the standard treatment for most of the patients without consideration of individual prognostic and predictive biomarkers.…”
mentioning
confidence: 99%